Relationship between moisture loss and physicochemical quality attributes of tomato under different storage conditions - Khalid, Samina; Ullah, Muhammad I; Khalid, Muhammad S; Shahid, Muhammad; Sultana, Syeda R (Journal of Postharvest Technology, 2024)
Moisture loss (ML) from fresh produce reduces its mass, appearance and quality, depends upon on surrounding’s temperature (T) and relative humidity (RH).The current study was designed to appraise the influence of storage conditions (SC) on tomato fruit quality and to develop relationship between ML and fruit quality under different SC. Freshly harvested tomato after washing and air drying were kept at ambient conditions and under zero energy cool chamber (ZECC) for fourteen days and analyzed on alternate days for fruit quality determination. ML (9.72%), total soluble solids (4.79 ◦Brix) and fruit internal temperature (29.29°C) was higher at ambient conditions and lower (3.23%, 4.59 ◦Brix and 25.12 °C, respectively) in ZECC. ML had significant negative relationship with ascorbic acid (r=-0.469 and r=-0.584) and significant positive relationship with internal temperature (r=0.834 and r=0.596) and pH (r=0.766 and r=0.542) of tomato in both ZECC and at ambient conditions respectively. ML and TSS had significant negative correlation (r=-0.498) in ZECC while, positive butt non-significant correlation (r=0.342) at ambient conditions.